Direct Numerical Simulation of Particle-Laden Swirling Flows on Turbulence Modulation. (25th May 2014) - Yan, Jie; Gui, Nan; Xie, Gongnan; Gao, Jinsen
Abstract : The modulation of turbulence by the laden particles in swirling flows is studied via direct numerical simulation. The statistical characteristics of turbulence modulation are investigated in detail under the effects of different mass loadings as well as Stokes numbers. It is found that the characteristics of turbulence modulation for different Stokes numbers are very similar to each other when the mass loading is light. As the mass loading increases, small particles seem to modulate turbulence more rapidly than large particles. The number concentration or the number flow rate of particles plays an important role in modulation of turbulence. It induces the preferential attenuation of turbulence for small particles in the near field region. Moreover, the trends of modulation of the axial/azimuthal fluctuations, the turbulent kinetic energy, and the Reynolds stress tenor as well as its invariants are similar in the near field region. However, when the turbulence is decayed sufficiently in the downstream region, the inverse turbulence modulation may occur especially for the regions with local intensive accumulation of small particles.